2011
DOI: 10.1208/s12249-011-9621-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing and Type of Mucosa on Ex Vivo Drug Permeability Parameters

Abstract: Abstract. The porcine esophageal mucosa has been proposed as a substitute for the buccal mucosa barrier on ex vivo permeability studies mainly due to its large surface area as well as its easier preparation. Therefore, this study compared the ex vivo permeability parameters of two drugs (carmabazepine (CBZ) and triamcinolone acetonide (TAC)) with different permeabilities and physicochemical properties through buccal and esophageal mucosae using a Franz diffusion cell system and HPLC as detection method. The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 20 publications
3
20
0
1
Order By: Relevance
“…Thus, a tissue sample from porcine buccal mucosa was fixed directly after slaughter at the abattoir, and no difference was found between the prefrozen and the fresh tissue samples. Previous studies have showed that a freezing cycle may influence the histology of the tissue, but not the permeability, which is in accordance with the findings of the present study wherein a histological comparison showed that fresh buccal mucosa, fixed just after slaughter, showed no difference to the prefrozen tissue sample (data not shown). The impact of the pH treatments during the permeability study was examined for the lowest and the highest pH values, that is, pH 7.4 and 9.0.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, a tissue sample from porcine buccal mucosa was fixed directly after slaughter at the abattoir, and no difference was found between the prefrozen and the fresh tissue samples. Previous studies have showed that a freezing cycle may influence the histology of the tissue, but not the permeability, which is in accordance with the findings of the present study wherein a histological comparison showed that fresh buccal mucosa, fixed just after slaughter, showed no difference to the prefrozen tissue sample (data not shown). The impact of the pH treatments during the permeability study was examined for the lowest and the highest pH values, that is, pH 7.4 and 9.0.…”
Section: Resultssupporting
confidence: 93%
“…The lower permeability of metoprolol in the human model could be because of (1) an adherent mucus gel layer acting as an additional barrier that might not be preserved in the prefrozen porcine model and/or (2) a difference in protein and/or lipid composition of the human and porcine tissue that affect the barrier properties. Evaluation of the difference in drug permeability using fresh and prefrozen tissues has been performed in numerous studies, and there is no consensus regarding the significance of freezing on the permeability of various drugs with different physicochemical properties. However, there is a general agreement that freezing of tissues does not affect the lipid permeability barrier, which is responsible for the barrier properties of small lipophilic molecules …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH (Model 215 pH meter; Denver Instrument, Bohemia, NY, USA) of the prepared formulations and formulations with different volume of artificial saliva are given in Table a,b, respectively. The artificial saliva solution was prepared using salts in DI water and adjusted to alkaline pH 7.2 …”
Section: Methodsmentioning
confidence: 99%
“…The mucosal membrane was carefully separated by removing the underlying connective tissues using surgical scissors. The separated mucosal membrane was washed with deionized water and then with simulated saliva (pH 6.2) [10] . Porcine buccal mucosa (3 cm diameter) was glued on the surface of a glass slab.…”
Section: Ex Vivo Mucoadhesion Timementioning
confidence: 99%